Human All Too Human: An examination of mind body relationship in Freudian theory (Existential Analysis: Journal of the Society for Existential Analysis, 2002)
The intention of this paper is to explore 'the' mind body relationship in Freud's writing and to contribute in some small way to a proposed revision of the basis of Freud's 'immortality' as we come to see him as human all too human. This paper sets out to challenge accepted wisdom about what Freud was striving to say and to question whether this has any basis in his work or, rather, whether it is largely the result of misinterpretation and what others have done with his ideas.